Decision Aids for Patients. - Lenz, Matthias; Buhse, Susanne; Kasper, Jürgen; Kupfer, Ramona; Richter, Tanja; Mühlhauser, Ingrid (Deutsches Ärzteblatt International, 2012)
Background: Patients want to be more involved in medical decision-making. To this end, some decision aids are now available. Methods: We present an overview of this subject, in which we explain the terms "shared decision-making", "decision aid", and "evidence- based patient information" and survey information on the available decision aids in German and other languages on the basis of a literature search in MEDLINE, EMBASE and PsycInfo and a current Cochrane Review. We also searched the Internet for providers of decision aids in Germany. Results: Decision aids exist in the form of brochures, decision tables, videos, and computer programs; they address various topics in the prevention, diagnosis, and treatment of disease. They typically contain information on the advantages and disadvantages of the available options, as well as guidance for personal decision-making. They can be used alone or as a part of structured counseling or patient education. Minimal quality standards include an adequate evidence base, completeness, absence of bias, and intelligibility. Our search revealed 12 randomized controlled trials (RCTs) of decision aids in German and 106 RCTs of decision aids in other languages. These trials studied the outcome of the use of decision aids not just with respect to clinical developments, but also with respect to patient knowledge, adherence to treatment regimens, satisfaction, involvement in decision-making, autonomy preference, and decisional conflicts. Conclusion: Only a small fraction of the available decision aids were systematically developed and have been subjected to systematic evaluation. Patients are still not receiving the help in decision-making to which medical ethics entitles them. Structures need to be put in place for the sustainable development, evaluation and implementation of high-quality decision aids.